Effects of Recombinant Toxoplasma gondii Citrate Synthase I on the Cellular Functions of Murine Macrophages In vitro - Liu, Xinchao; Ma, Qunshan; Sun, Xiaoni; Lu, Mingmin; Ehsan, Muhammad; Hasan, Muhammad Waqqas; Xu, Lixin; Yan, RuoFeng; Song, XiaoKai; Li, XiangRui (Frontiers in Microbiology, 2017)
Toxoplasmosis, which is one of the most widespread zoonoses worldwide, has a high incidence and infection can result in severe disease in humans and livestock. Citrate synthase (CS) is a component of nearly all living cells that plays a vital role in the citric acid cycle, which is the central metabolic pathway of aerobic organisms. In the present study, the citrate synthase I gene of Toxoplasma gondii (T. gondii) (TgCSI) was cloned and characterized. The TgCSI gene had an open reading frame of 1665 bp nucleotides encoding a 555 amino acid protein with a molecular weight of 60 kDa. Using western blotting assay, the recombinant protein was successfully recognized by the sera of rats experimentally infected with T. gondii, while the native protein in the T. gondii tachyzoites was detected in sera from rats immunized with the recombinant protein of TgCSI. Binding of the protein to murine macrophages was confirmed by immuno fluorescence assay. Following incubation of macrophages with rTgCSI, the rTgCSI protein was found to have a dual function, with low concentrations (5-10 µg/mL) enhancing phagocytosis and high levels (80 µg/mL) inhibiting phagocytosis. Investigation of murine macrophage apoptosis illustrated that 5 µg/mL rTgCSI protein can significantly induce early apoptosis and late stage apoptosis (*p<0.05), while 10 µg/mL rTgCSI protein significantly induced early apoptosis, but had no effect on late stage of apoptosis (**p<0.01), and 80 µg/mL rTgCSI protein inhibited late stage apoptosis of macrophages (*p<0.05). Cytokine detection revealed that the secretion of interleukin-10, interleukin-1β, transforming growth factor-β1 and tumor necrosis factor-α of macrophages increased after the cells were incubated with all concentration of rTgCSI, with the exception that 5 µg/mL rTgCSI had no effect on the secretion of interleukin-10 and interleukin-1β. However, secretion of NO and cell proliferation of the macrophages were substantially reduced. Taken together, these results suggested that TgCSI can affect the immune functions of murine macrophages by binding to the cells in vitro.